Health benefits of reduced patient cost sharing in Japan - Akihiro Nishi; J Michael McWilliams; Haruko Noguchi; Hideki Hashimoto; Nanako Tamiya; Ichiro Kawachi (The World Health Organization, 2012)
OBJECTIVE: To assess the effect on out-of-pocket medical spending and physical and mental health of Japan's reduction in health-care cost sharing from 30% to 10% when people turn 70 years of age. METHODS: Study data came from a 2007 nationally-representative cross-sectional survey of 10 293 adults aged 64 to 75 years. Physical health was assessed using a 16-point scale based on self-reported data on general health, mobility, self-care, activities of daily living and pain. Mental health was assessed using a 24-point scale based on the Kessler-6 instrument for nonspecific psychological distress. The effect of reduced cost sharing was estimated using a regression discontinuity design. FINDINGS: For adults aged 70 to 75 years whose income made them ineligible for reduced cost sharing, neither out-of-pocket spending nor health outcomes differed from the values expected on the basis of the trend observed in 64- to 69-year-olds. However, for eligible adults aged 70 to 75 years, out-of-pocket spending was significantly lower (P < 0.001) and mental health was significantly better (P < 0.001) than expected. These differences emerged abruptly at the age of 70 years. Moreover, the mental health benefits were similar in individuals who were and were not using health-care services (P = 0.502 for interaction). The improvement in physical health after the age of 70 years in adults eligible for reduced cost-sharing tended to be greater than in non-eligible adults (P = 0.084). CONCLUSION: Reduced cost sharing was associated with lower out-of-pocket medical spending and improved mental health in older Japanese adults.